2006
DOI: 10.1159/000090953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Occupational Therapy Program on Functional Outcomes in Older Stroke Patients

Abstract: Background: During the last decade, occupational therapy has gained increasing importance as component of the rehabilitation programs in disabled patients. Objective: To evaluate the efficacy of occupational therapy programs in patients with a recent stroke. Methods: We selected all patients with a primary diagnosis of ischemic stroke (n = 50) consecutively admitted to the two post-acute Geriatric Rehabilitation Units (CEMI 2 and 3) of the ‘A. Gemelli’ Hospital – Catholic University of Sacred Heart, Rome, Ital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
8
0
4
Order By: Relevance
“…463 Teasell and colleagues 464 reported that even severely impaired individuals can make gains in ADL performance with extended rehabilitation designed for their tolerance levels; unfortunately, such extended rehabilitation is not typically provided in the US healthcare system. Collectively, the evidence suggests that ADL and IADL training results in greater ADL and IADL independence than no ADL or IADL training [167][168][169][170][171] (but see Logan et al 465 ). Furthermore, Liu and colleagues 466 reported that training stroke patients to mentally rehearse ADL sequences and related problem solving resulted in even greater ADL gains than ADL training alone.…”
Section: Treatment In Inpatient Settingsmentioning
confidence: 99%
“…463 Teasell and colleagues 464 reported that even severely impaired individuals can make gains in ADL performance with extended rehabilitation designed for their tolerance levels; unfortunately, such extended rehabilitation is not typically provided in the US healthcare system. Collectively, the evidence suggests that ADL and IADL training results in greater ADL and IADL independence than no ADL or IADL training [167][168][169][170][171] (but see Logan et al 465 ). Furthermore, Liu and colleagues 466 reported that training stroke patients to mentally rehearse ADL sequences and related problem solving resulted in even greater ADL gains than ADL training alone.…”
Section: Treatment In Inpatient Settingsmentioning
confidence: 99%
“…Occupational therapy is dominant in assisting people to engage in daily life activities and is an integral part of comprehensive rehabilitation (Landi et al, 2006).…”
Section: Problem Statementmentioning
confidence: 99%
“…Em um estudo randomizado sobre a efetividade da intervenção, Graff et al (2006) concluem que a Terapia Ocupacional melhora a funcionalidade diária do paciente com demência, além de reduzir a sobrecarga do cuidador. Já para pacientes com sequela de acidente vascular encefálico, estudos de Steultjens et al (2003) e Landi et al (2006) concluem que os pacientes atendidos pelos terapeutas ocupacionais apresentam maiores níveis de independência em atividades de vida diária. resgate e/ou descoberta de atividades significativas, reabilitação cognitiva, adequação do ambiente e do funcionamento domiciliar, orientação aos familiares e cuidadores.…”
Section: Intervenção Terapêutica Ocupacional: Da Teoria à Práticaunclassified